The S‐layer proteins of Tannerella forsythia are secreted via a type IX secretion system that is decoupled from protein O‐glycosylation. (15th September 2014) - Tomek, M.B.; Neumann, L.; Nimeth, I.; Koerdt, A.; Andesner, P.; Messner, P.; Mach, L.; Potempa, J.S.; Schäffer, C.
Summary Conserved C‐terminal domains (CTD) have been shown to act as a signal for the translocation of certain proteins across the outer membrane of Bacteroidetes via a type IX secretion system (T9SS). The genome sequence of the periodontal pathogen Tannerella forsythia predicts the presence of the components for a T9SS in conjunction with a suite of CTD proteins. T. forsythia is covered with a two‐dimensional crystalline surface (S‐) layer composed of the glycosylated CTD proteins TfsA and TfsB. To investigate, if T9SS is functional in T. forsythia, T9SS‐deficient mutants were generated by targeting either TF0955 (putative C‐terminal signal peptidase) or TF2327 (PorK ortholog), and the mutants were analyzed with respect to secretion, assembly and glycosylation of the S‐layer proteins as well as proteolytic processing of the CTD and biofilm formation. In either mutant, TfsA and TfsB were incapable of translocation, as evidenced by the absence of the S‐layer in transmission electron microscopy of ultrathin‐sectioned bacterial cells. Despite being entrapped within the periplasm, mass spectrometry analysis revealed that the S‐layer proteins were modified with the complete, mature glycan found on the secreted proteins, indicating that protein translocation and glycosylation are two independent processes. Further, the T9SS mutants showed a denser biofilm with fewer voids compared with the wild‐type. This study demonstrates the functionality of T9SS and the requirement of CTD for the outer membrane passage of extracellular proteins in T. forsythia, exemplified by the two S‐layer proteins. In addition, T9SS protein translocation is decoupled from O‐glycan attachment in T. forsythia.